(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Ortega’s liberalism has not been studied taking into consideration its philosophical foundations and in the different phases of Ortega´s thought. From neokantism, Ortega thinks about liberalism as an ideal or law of morality. Later on, from “phenomenology” and in the origins of ratiovitalisms, in the period of 1914, Ortega did not conceive of freedom as a moral duty but as something related to the idea of having to be a person in a vital world (Lebenswelt). In a third period, from 1929 on, Ortega thinks about freedom as a sentiment or radical idea about life in the context of his metaphysics of human life as radical reality, the first one and essential.